Seasonality of coastal upwelling trends under future warming scenarios along the southern limit of the canary upwelling system. (April 2017) - Sousa, Magda Catarina; Alvarez, Ines; deCastro, Maite; Gomez-Gesteira, Moncho; Dias, João Miguel
Highlights: New findings about future Canary upwelling trends seasonality and SST response. Heterogeneity of Canary upwelling future trends throughout the year. Intensification of Canary upwelling index projected from October to April. Low warming rates projected for SST along Canary coast. Higher warming rates for summer SST trends induced by upwelling index weakening. Abstract: The Canary Upwelling Ecosystem (CUE) is one of the four most important upwelling sites around the world in terms of primary production, with coastal upwelling mostly a year-round phenomenon south of 30°N. Based on annual future projections, several previous studies indicated that global warming will intensify coastal upwelling in the northern region and will induce its weakening at the southernmost latitudes. However, analysis of historical data, showed that coastal upwelling depends on the length of the time series, the season, and even the database used. Thus, despite previous efforts, an overall detailed description of seasonal upwelling trends and their effects on sea surface temperature (SST) along the Canary coast over the 21st century remains unclear. To address this issue, several regional and global wind and SST climate models from CORDEX and CMIP5 projects for the period 1976–2099 were analyzed. This research provides new insights about coastal upwelling trends under future warming scenarios for the CUE, with results showing opposite patterns for upwelling index (UI) trends depending on the season. A weakening of the UI occurs from May to August all along the coast, whereas it increases from October to April. Analysis of SST trends reveals a general warming throughout the area, although the warming rate is considerably lower near the shore than at open ocean locations due to coastal upwelling effects. In addition, SST projections show higher warming rates from May to August than from October to April in response to the future decreasing trend in the UI during the summer months.